2021
DOI: 10.1002/biot.202100156
|View full text |Cite
|
Sign up to set email alerts
|

Sterilization of sealed PVDF pouches containing decellularized scaffold by electrical stimulation

Abstract: A terminal sterilization process for tissue engineering products, such as allografts and biomaterials is necessary to ensure complete removal of pathogenic microorganisms such as the bacteria, fungi, and viruses. However, it can be difficult to sterilize allografts and artificial tissue models packaged in wet conditions without deformation. In this study, we investigated the sterilization effects of electrical stimulation (ES) and assessed its suitability by evaluating sterility assurance levels in pouches at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…The effect of ES on various microorganisms such as Escherichia coli , Staphylococcus aureus , and Pseudomonas aeruginosa can be inhibitory, stimulatory, or none depending on the parameters and modes selected ( Caubet et al., 2004 ; Dusane et al., 2019 ; Lee et al., 2021 ). Studies showed that the mechanisms of ES for promoting wound healing might include increased angiogenesis and circulation as well as a direct antibacterial effect of ES ( Gentzkow, 1993 ; Asadi and Torkaman, 2014 ; Ashrafi et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ES on various microorganisms such as Escherichia coli , Staphylococcus aureus , and Pseudomonas aeruginosa can be inhibitory, stimulatory, or none depending on the parameters and modes selected ( Caubet et al., 2004 ; Dusane et al., 2019 ; Lee et al., 2021 ). Studies showed that the mechanisms of ES for promoting wound healing might include increased angiogenesis and circulation as well as a direct antibacterial effect of ES ( Gentzkow, 1993 ; Asadi and Torkaman, 2014 ; Ashrafi et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%